Efficient synthesis of 3,6,13,16-tetrasubstituted-tetrabenzo[a,d,j,m]coronenes by selective C–H/C–O arylations of anthraquinone derivatives - Terai, Seiya; Sato, Yuki; Kochi, Takuya; Kakiuchi, Fumitoshi (Beilstein Journal of Organic Chemistry, 2020)
An efficient synthesis of tetrabenzo[a,d,j,m]coronene derivatives having alkyl and alkoxy substituents at the 3, 6, 13, and 16-positions was achieved based on the ruthenium-catalyzed coupling reactions of anthraquinone derivatives with arylboronates via C–H and C–O bond cleavage. The reaction sequence involving the arylation, carbonyl methylenation, and oxidative cyclization effectively provided various tetrabenzo[a,d,j,m]coronenes in short steps from readily available starting materials. Tetrabenzo[a,d,j,m]coronenes possessing two different types of substituents were obtained selectively by sequential chemoselective C–O arylation and C–H arylation. The 1H NMR spectra of the tetrabenzo[a,d,j,m]coronene product indicated its self-assembling behavior in CDCl3.
Keywords: C–H arylation; C–O arylation; oxidative cyclization; polycyclic aromatic hydrocarbons; ruthenium catalyst

(untitled) - Grimsdale, A. C.; Leok Chan, K.; Martin, R. E.; Jokisz, P. G.; Holmes, A. B. (Chem. Rev., 2009)

(untitled) - Feng, F.; Liu, L.; Wang, S. (Nat. Protoc., 2010)

(untitled) - Wang, C.; Dong, H.; Hu, W.; Liu, Y.; Zhu, D. (Chem. Rev., 2012)

(untitled) - Narita, A.; Wang, X.-Y.; Feng, X.; Müllen, K. (Chem. Soc. Rev., 2015)

Cross-Coupling Reactions: A Practical Guide - Miyaura, N. (2002)

(untitled) - Martin, R.; Buchwald, S. L. (Acc. Chem. Res., 2008)

Applied Cross-Coupling Reactions - Nishihara, Y. (Springer, 2013)

Metal-Catalyzed Cross-Coupling Reactions and More - de Meijere, A.; Bräse, S.; Oestreich, M. (Wiley-VCH, 2014)

(untitled) - Tobisu, M.; Chatani, N. (Acc. Chem. Res., 2015)

(untitled) - Hussain, I.; Singh, T. (Adv. Synth. Catal., 2014)

(untitled) - Kuninobu, Y.; Sueki, S. (Synthesis, 2015)

(untitled) - Segawa, Y.; Maekawa, T.; Itami, K. (Angew. Chem., Int. Ed., 2015)

New Trends in Cross-Coupling: Theory and Applications - Sharma, U.; Modak, A.; Maity, S.; Maji, A.; Maiti, D. (Direct arylation via C–H activation, 2015)

(untitled) - Zha, G.-F.; Qin, H.-L.; Kantchev, E. A. B. (RSC Adv., 2016)

(untitled) - Hagui, W.; Doucet, H.; Soulé, J.-F. (Chem, 2019)

(untitled) - Kitazawa, K.; Kochi, T.; Sato, M.; Kakiuchi, F. (Org. Lett., 2009)

(untitled) - Kitazawa, K.; Kochi, T.; Nitani, M.; Ie, Y.; Aso, Y.; Kakiuchi, F. (Chem. Lett., 2011)

(untitled) - Matsumura, D.; Kitazawa, K.; Terai, S.; Kochi, T.; Ie, Y.; Nitani, M.; Aso, Y.; Kakiuchi, F. (Org. Lett., 2012)

(untitled) - Suzuki, Y.; Yamada, K.; Watanabe, K.; Kochi, T.; Ie, Y.; Aso, Y.; Kakiuchi, F. (Org. Lett., 2017)

(untitled) - Izumoto, A.; Kondo, H.; Kochi, T.; Kakiuchi, F. (Synlett, 2017)

(untitled) - Kakiuchi, F.; Kan, S.; Igi, K.; Chatani, N.; Murai, S. (J. Am. Chem. Soc., 2003)

(untitled) - Kakiuchi, F.; Matsuura, Y.; Kan, S.; Chatani, N. (J. Am. Chem. Soc., 2005)

(untitled) - Kitazawa, K.; Kotani, M.; Kochi, T.; Langeloth, M.; Kakiuchi, F. (J. Organomet. Chem., 2010)

(untitled) - Hiroshima, S.; Matsumura, D.; Kochi, T.; Kakiuchi, F. (Org. Lett., 2010)

(untitled) - Ogiwara, Y.; Miyake, M.; Kochi, T.; Kakiuchi, F. (Organometallics, 2017)

(untitled) - Koseki, Y.; Kitazawa, K.; Miyake, M.; Kochi, T.; Kakiuchi, F. (J. Org. Chem., 2017)

(untitled) - Suzuki, I.; Kondo, H.; Kochi, T.; Kakiuchi, F. (J. Org. Chem., 2019)

(untitled) - Kakiuchi, F.; Usui, M.; Ueno, S.; Chatani, N.; Murai, S. (J. Am. Chem. Soc., 2004)

(untitled) - Ueno, S.; Mizushima, E.; Chatani, N.; Kakiuchi, F. (J. Am. Chem. Soc., 2006)

(untitled) - Ogiwara, Y.; Kochi, T.; Kakiuchi, F. (Org. Lett., 2011)

(untitled) - Kondo, H.; Akiba, N.; Kochi, T.; Kakiuchi, F. (Angew. Chem., Int. Ed., 2015)

(untitled) - Kondo, H.; Kochi, T.; Kakiuchi, F. (Org. Lett., 2017)

(untitled) - Kondo, H.; Kochi, T.; Kakiuchi, F. (Chem. – Eur. J., 2020)

(untitled) - Feng, X.; Pisula, W.; Müllen, K. (Pure Appl. Chem., 2009)

(untitled) - Hopf, H. (Chem. Rec., 2014)

(untitled) - Zhang, Q.; Peng, H.; Zhang, G.; Lu, Q.; Chang, J.; Dong, Y.; Shi, X.; Wei, J. (J. Am. Chem. Soc., 2014)

(untitled) - Hirose, T.; Miyazaki, Y.; Watabe, M.; Akimoto, S.; Tachikawa, T.; Kodama, K.; Yasutake, M. (Tetrahedron, 2015)

(untitled) - Witte, G.; Wöll, C. (J. Mater. Res., 2004)

(untitled) - Wu, J.; Pisula, W.; Müllen, K. (Chem. Rev., 2007)

(untitled) - Ren, S.; Yan, C.; Vak, D.; Jones, D. J.; Holmes, A. B.; Wong, W. W. H. (Adv. Funct. Mater., 2012)

(untitled) - Wong, W. W. H.; Subbiah, J.; Puniredd, S. R.; Purushothaman, B.; Pisula, W.; Kirby, N.; Müllen, K.; Jones, D. J.; Holmes, A. B. (J. Mater. Chem., 2012)

(untitled) - Dumslaff, T.; Yang, B.; Maghsoumi, A.; Velpula, G.; Mali, K. S.; Castiglioni, C.; De Feyter, S.; Tommasini, M.; Narita, A.; Feng, X.; Müllen, K. (J. Am. Chem. Soc., 2016)

(untitled) - Zhang, X.; Jiang, X.; Zhang, K.; Mao, L.; Luo, J.; Chi, C.; Chan, H. S. O.; Wu, J. (J. Org. Chem., 2010)

(untitled) - Pola, S.; Kuo, C.-H.; Peng, W.-T.; Islam, M. M.; Chao, I.; Tao, Y.-T. (Chem. Mater., 2012)